High frequency response to the impedance complex properties of Nb-doped CaCu3Ti4O12 electroceramics. - Sulaiman, Muhammad Azwadi; Hutagalung, Sabar D.; Mohamed, Julie J.; Ahmad, Zainal A.; Ain, Mohd Fadzil; Ismail, Bakar (2011)
Impedance analyses was performed on undoped and Nb-doped CaCu3Ti4O12 (CaCu3Ti4−xNbxO12+x/2; x=0, 0.01, 0.03, 0.05, 0.1) to investigate their electrical properties. The pellet samples were prepared using the solid state reaction method. Silver electrode was deposited on both pellets’ surfaces for electrical measurement. The thermally etched samples showed tiny bumped domains within the grains. The exis- tence of both domain and grain boundaries are believed to strongly influence the dielectric constant of CaCu3Ti4O12 (CCTO). Undoped CCTO showed two arcs of impedance complex plane while Nb-doped sam- ples have three arcs. Each arc represents the constituent elements of the CCTO. The highest frequency arc is evidence that CCTO consists of conductive domains which measure about 1?and are insulated by two types of barriers, i.e. domain boundary and grain boundary.